Reliance goes public for the first time by announcing its IPO - Reliance Industries Limited (2022)
Reliance goes public for the first time by announcing its IPO and raises Rs 2.8 crore (USD 3.28 million), thus ushering in the Equity Cult in India. • Initial share price is Rs 10 • Issue oversubscribed seven times with 58,000 investors by the year end • Receives approval for BSE listing of Reliance as Reliance Textile Industries Ltd.